Character Education in Ranup Lampuan Dance: A Critical Study of Non-Verbal Communication - Fathul Futuh; Al Farahil A’la (Universitas Muhammadiyah Yogyakarta, 2023)
The Ranup Lampuan dance was created by Yuslizar in Banda Aceh in 1959. Yuslizar’s Ranup Lampuan dance is danced to honor and welcome guests officially. In the show, seven female dancers wear traditional clothes and dance with gentle movements while carrying a puan and betel as a sign of respect. This dance is full of meanings and values that reflect the uniqueness of the culture and customs of the Acehnese in honoring guests. This study will look at the meaning of non-verbal messages contained in the Ranup Lampuan dance through the choreography of the movements and clothing used. This research was conducted on the younger generation of dancers, musicians and dance fashion stylists of Ranup Lampuan. This research uses descriptive qualitative research with a phenomenological approach. The results show that the non-verbal message of the Ranup Lampuan dance movement, which is danced regularly, uniformly, gentle, and graceful with a beautiful smile throughout the performance, has a non-verbal meaning that implies “rumeh muka” which means friendly in welcoming guests, and implies cohesiveness and cooperation, as well as Islamic values related to procedures for honoring guests in every activity of Acehnese life. Non-verbal messages through the clothes worn can be seen from the choice of colors, uniformity of clothing, selection of dance accessories, and clothing equipment used in the Ranup Lampuan dance reflecting courage, cohesiveness, beauty, neatness, attractiveness and diversity and Islamic values in Acehnese.